Factors influencing the occurrence and inheritance of cancer in different parts of India: A survey research - BHASKAR JYOTI DAS; AKSHADA BHUJBAL; PRAJAKTA GAOPANDE (International Journal of Pharma and Bio Sciences, 2019)
Cancer is a group of complex diseases which emanates by gradual accumulation of genetic defects resulting in bereavement of cell’s genetic stability and thereby compelling them to become immortal. Cancer possesses a worldwide threat and it has been estimated feasibly to witness an increase in a greater number of cancer cases by the next two decades. Besides the decisive role of genes in transmission of cancer to the next generation, cancer also has eminent environmental influences that together define the disease as multifactorial. This study involves systematic data collection through a reporting proforma and interpretation which reveals the prevalence of cancer in different parts of India. In this research study, parameters such as age of cancer patients, cancer site, diseases found along with cancer, food habits, gender of cancer patients, history of genetic diseases, lifestyle, occupation, smoking and alcohol consumption, cancer stages, state wise cancer prevalence and tumor locations, were analyzed and taken into consideration. Many elements like a person’s diet, immunity, physiology; and environmental factors such as water, temperature, ozone layer degradation; contribute in a different way for tumor formation and the origin of cancer. People with older ages and those associated with different diseases and disorders are more prone to cancer than any other age groups. This study put efforts to familiarize the people about the numerous risk factors associated with cancer, referred from our collected data. This study also may greatly influence the lowering of cancer risks and help in combating the disease with fair and efficient management techniques in any situation